Comparison of in-vitro and in-vivo parameters of whole blood derived random donor platelets (RDP) after over-night hold with RDP prepared after 2-h hold: Single centre report from India. (December 2021) - Tiwari, Aseem K.; Marik, Arghyadeep; Aggarwal, Geet; Pabbi, Swati; Harith, Arun Kumar; Aggarwal, Divyajyoti; Singh, Bhupender
Abstract: Background: Random Donor Platelet (RDP) derived from whole blood is the major source of platelets in India. At our centre, we prepare RDPs by buffy coat method after a holding period of 2-hours (THRDP) as per current regulatory guidelines. Overnight hold of buffy coats before RDP preparation (OHRDP) would logistically optimise the manpower usage at our centre. The aim of this study was to compare both in-vitro as well as in-vivo parameters of OHRDPs with THRDPs. Methodology: Hematological (Platelet, leucocyte counts), physical (pH and Swirling) and biochemical parameters (pO2, pCO2, lactate, bicarbonate and glucose) as well as platelet activation markers were tested in THRDPs and OHRDPs each at Day-1 and Day-5 as in-vitro studies. Separately, in-vivo study was done where Corrected count increment (CCI) and percentage platelet recovery (PPR) were considered. All parameters were expressed as Mean ± Standard deviation and were analysed using paired t -test with level of significance, p < 0.05. Results: OHRDPs had higher platelet counts and lower leucocytes and CD62 P expression than THRDPs. All other markers were well within the quality control range in both groups. No significant differences were seen in the two groups when comparing CCI and PPR. Conclusion: OHRDPs were found to be as good or better as compared to the THRDPs in the in-vitro part of our study. Additionally, there were no significant differences between the two groups when they were compared in vivo. This makes us conclude that overnight hold of buffy coats may be implemented at our center.